Retrospective study of the impact of unrecognised Kawasaki disease, coronary aneurysm and ectasia. (1st December 2017) - Waterhouse, Benjamin R.; Tulloh, Robert M.R.; Kim, Yongcheol; Creasy, Will; Adlam, David; Johnson, Thomas W.
Abstract: Background: Coronary artery aneurysms resulting from unrecognised or untreated Kawasaki Disease (KD) have thrombotic and stenotic potential leading to myocardial infarction. We aimed to characterise the prevalence and outcomes of patients presenting to a UK-based adult tertiary cardiology service with angiographic evidence of aneurysm or ectasia. Methods: Retrospective review was undertaken of reports and original coronary angiograms in all patients under 50 years old undergoing coronary angiography between 2011 and 2015. Aneurysm/ectasia were defined by calibre discrepancy > 1.5 × and the number of segments involved. Aneurysms were categorised as being probable, or unlikely to represent unrecognised KD. Results: Aneurysm or ectasia was observed in 49 of 1578 patients (3.7%). Eleven patients had angiographic findings consistent with probable antecedent KD (0.8%), a further 18 patients had evidence of coronary artery aneurysm (1.4%) and ectasia was observed in 20 patients (1.5%). The commonest mode of presentation was ST elevation myocardial infarction, observed in 71.4% of patients. Review of angiogram written reports demonstrated a spurious application of the terms aneurysm and ectasia, with a sensitivity of 10.3% & 55.0%, and a positive predictive value of reporting of 50.0% & 52.4%, respectively. Conclusions: As the first UK study to characterise the angiographic prevalence of Kawasaki Disease, both aneurysm and ectasia were observed with a relatively low frequency. However, their presence is associated with high-risk acute ischaemic presentations. Furthermore, we demonstrated a poor level of reporting of coronary abnormalities and advocate an increased awareness of Kawasaki disease and coronary aneurysm/ectasia amongst adult cardiologists.